Perspectives on hospitality industry trade unionism in the UK and beyond - Roy C. Wood (Research in Hospitality Management, 2020)
The study of traditional industrial relations institutions in the hospitality industry (such as trade unions) is somewhat in the doldrums. This is, perhaps, unsurprising, given that the sector has historically never had high union membership. This article briefly explores the general influence of trade unions today in terms of overall membership and the concept of union density. The observed decline in the numerical (membership) strength of unions and their influence is clearly attributable to the — albeit uneven — pursuit of conservative economic policies over the last half-century. Membership of trade unions in the hospitality industry has also remained low but not collapsed completely. Extant explanations for the absence of union activity in an industry notorious for its poor conditions of employment are recounted and, employing secondary data from a number of sources, an effort is made to contextualise the present state of trade union membership and activity in the hospitality sector.